the degree of informantional litracy skills related to (accessing information, orginazing and using information and evaluating information)of high education students at Damascus university according to some variables - al abdallah, Fawaz; aldebal, Walaa (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The research aims to determine the degree of litracy informantion skills related to (accessing information, orginazing and using information and evaluating information) of high education students at Damascus university by applying the informational litracy scalepreparedby researcher for 100 students according to the following variables(gender, scientific level and type of faculity) , for the academic year 2014/2015 the researcher reached the following results: the degree of informational literacy reached (78,98) for the higher education students which is a very good degree as the results show that there is statistaclly significant difference at a significant level (0,05) can be attributed to veriable of gender infavor of males and there is statistaclly significant difference at a significant level (0,05) can be attributed to variable of scientifical level infavor of PHD students but there is no statistaclly significant difference at a significant level (0,05) can be attributed to variable of type of faculty (scientific, humanistic), The research gave suggestions which provide to students methodes to access information, organize and use information as well as to evaluate the information, and focus on providing informational litracy skills to students according to programs carried out by faculties and ministry of high education.